From Massacre Creek to Slaughter Hill: The tracks of Mystery Road. Issue 1 (2nd January 2016) - Kirkpatrick, Peter
ABSTRACT: Ivan Sen's 2013 feature Mystery Road [dir., 2013. Sydney: Mystery Road Films] seeks to break out of the arthouse mould of most Aboriginal cinema in its calculated adaptation of two seemingly disparate Hollywood genres, film noir and the western: genres which are foregrounded in the style and marketing of the film. Aaron Pedersen in his starring role as 'Indigenous cowboy detective' Jay Swan strikes a delicate balance between his compromised role as agent of the state and as freewheeling hero, for his role as a detective is underpinned by the 'treacherous' historical legacy of the tracker. In this article, I trace the central importance of the tracker figure in a reading of Mystery Road, taking in, among other texts, Sen's 1999 film Wind [dir., 1999. Australia: Mayfan Film Productions] and Arthur Upfield's 'Bony' novels. The troubled status of the tracker feeds into the noirish elements of Mystery Road, which ultimately requires a new kind of hero to emerge so that retribution may be enacted for past and present wrongs. That hero is the cowboy, a part for which Pedersen has been dressed all along.